Monadic Second-Order Logic, Graphs and Unfoldings of Transition Systems - Courcelle, Bruno; Walukiewicz, Igor (BRICS Report Series, 1995)
We prove that every monadic second-order property of the unfolding of a transition system is a monadic second-order property of the system itself. We prove a similar result for certain graph coverings.